Na₂SO₃ Salt Effect on The Ionic Conductivity of Solid Polymer Electrolyte (SPE) Based on Polyvinyl Alcohol - Sylvia Ayu Pradanawati; Albert Turnip; Nur Laila Hamidah; Yose Fachmi Buys (Jurnal Kimia Sains dan Aplikasi, 2024)
This research is about solid polymer electrolyte (SPE) based on polyvinyl alcohol (PVA) synthesized using a solution casting technique by adding variations of sodium sulfite salt and glycerol as fillers to reduce the samples' bulk resistance for electrochemical energy storage application. The method used is a quantitative analysis based on the test results. X-ray Diffraction (XRD) was used to determine the crystallinity and structure of the solid polymer electrolyte material. Interactions between Na+ ions from salts in SPE were analyzed using Fourier transform infrared (FTIR). The mechanical properties of the SPE samples were analyzed using tensile testing (ultimate tensile strength). Solid polymer electrolyte (SPE) ion conductivity was analyzed using electrochemical impedance spectroscopy (EIS) with temperature variations of 25, 40, 50, 60, and 70°C. The maximum SPE ionic conductivity value is 1.05 × 10-5 S cm-1 in a PVA-Glycerol-Na2SO3 15% sample at 70°C.